Despedida del Comité Editorial (2015 - 2024) - Íñiguez-Rueda, Lupicinio; Araujo Jiménez, Eva Angelina; Carlotto, Mary Sandra; Estaún, Santiago; Núñez, Carmen Gloria; Peñaranda-Cólera, María del Carmen; Posocco, Silvia (Quaderns de Psicologia, 2025)
Despedida del Comité Editorial (2015 - 2024)